The Phase Transition in Natural Gypsum - M. KILIC, AHMET; KILIC, OZEN (Asian Journal of Chemistry, 2010)
In present study, the thermal behaviour of calcined gypsum specimens at temperature controlled laboratuar farin in the temperature range 120-1000ºC in atmospheric pressure by means of X-ray difractometer and scanning electron microscopy is examined. In this investigations, powder gypsum and calcined powder gypsum at different temperatures (120, 160, 180, 200, 250, 600 and 1000ºC) were used. Scanning electron microscopy observations and X-ray diffractometer results show that the transformation to bassanite (calcium sulfate hemihydrate) begins at ca. 120ºC, the transformation to anhydride complete at ca. 600ºC. Differential thermogram result was pulsed at these transformations.